Local power and globalization: social empowerment and the protection of natural heritage in brazilian federalismo / Poder local e globalização: o empoderamento social e a proteção do patrimônio natural no federalismo brasileiro - Garbaccio, Grace Ladeira; Marin, Jeferson Dytz; Biehl, Jamile Brunie (Revista de Direito da Cidade, 2021)
Abstract The Federal Constitution of 1988 of the Federative Republic of Brazil, in its provisions, provided the municipalities with autonomy to conduct local socioeconomic development and land use planning, aiming at the healthy quality of life of the population and sustainable development of the place. This article draws some lines on the importance of the use of municipal laws as tools of local environmental protection. Based on the research line Globalization, Environmental Law, Public Policies and Socioeconomic Development, the objective is to discuss and enable a relationship between the legitimacy of local power and popular participation when using environmental impact mitigation tools to prior planning within the Municipalities and the effective environmental preservation through the use of the current environmental legislation. Thus, through the analysis of land use and occupation of an intentional area of the Municipality of Montenegro - Rio Grande do Sul, it was confirmed the premise that in the region, because it has a wide standardization with the scope of protecting the areas of environmental restriction and previous studies on land use and management that allowed for public participation in decision-making processes, the municipality controls significantly the advances of urban expansion on the areas of environmental restriction, verifying that through participatory democracy it is possible for the local power to decide on the matters to their local peculiarities, which generates the empowerment of the common citizen and fosters the feeling of belonging and protection to the place that is inserted. Keywords: Environment; Municipal Planning; Local Power Resumo A Constituição Federal de 1988 da República Federativa do Brasil, em seus dispositivos, dotou de autonomia os Municípios para que estes conduzissem práticas locais de planejamento de desenvolvimento socioeconômico e ordenação de uso do solo, visando a sadia qualidade de vida da população e o desenvolvimento sustentável do local. O presente artigo traça algumas linhas sobre a importância da utilização de leis municipais como ferramentas de proteção ambiental local. Partindo-se da linha de pesquisa globalização, Direito Ambiental, Políticas Públicas e Desenvolvimento Socioeconômico, o objetivo é discutir e possibilitar que se estabeleça uma relação entre a legitimação do poder local e da participação popular quando da utilização dos instrumentos de mitigação dos impactos ambiental ao planejamento prévio dentro dos Municípios e a efetiva preservação ambiental através da utilização da legislação ambiental vigente. Desse modo, através da análise de uso e ocupação do solo de uma área intencional do Município de Montenegro – Rio Grande do Sul foi confirmado a premissa de que na região, por possuir uma vasta normatização com o escopo de tutelar as áreas de restrição ambiental e estudos prévios de uso e ordenação do solo que possibilitaram a participação Pública nos processos decisórios, o Município controla significativamente os avanços de expansão urbana sobre as áreas de restrição ambiental, verificando-se que por meio da democracia participativa é possível ao poder local decidir sobre as matérias afeitas as suas peculiaridades locais, que gera o empoderamento do cidadão comum e acalenta o sentimento de pertencimento e proteção ao local que está inserido. Palavras-chaves: Meio Ambiente; Planejamento Municipal; Poder Local.